2017
DOI: 10.1002/2016jb013684
|View full text |Cite
|
Sign up to set email alerts
|

Fractal density modeling of crustal heterogeneity from the KTB deep hole

Abstract: Fractal or multifractal concepts have significantly enlightened our understanding of crustal heterogeneity. Much attention has focused on 1/f scaling natures of physicochemical heterogeneity of Earth crust from fractal increment perspective. In this study, fractal density model from fractal clustering point of view is used to characterize the scaling behaviors of heterogeneous sources recorded at German Continental Deep Drilling Program (KTB) main hole, and of special contribution is the local and global multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 69 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…where P o is the specific pore volume of immature cotton fibers having the primary cell wall only, D v is the fractal dimension; E = 3 is the Euclidean dimension. Similarly, the dependence of the apparent density on the scale factor, F, is the following [7,14]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where P o is the specific pore volume of immature cotton fibers having the primary cell wall only, D v is the fractal dimension; E = 3 is the Euclidean dimension. Similarly, the dependence of the apparent density on the scale factor, F, is the following [7,14]:…”
Section: Resultsmentioning
confidence: 99%
“…Previously, the fractal theory was applied to analyze the porous structure of various materials [7][8][9][10]. In particular, for cellulose it was found that the process of nitrogen sorption by pores of various sizes can be described by a fractal with dimension from 2.1 to 2.5 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, such densities have been applied for many time in the understanding of many phenomena, such as climate factors distributions in different regions, crashes propagation and the effect on markets, etc. See [1,7,22,24,39,42]. These applications have been tackled by using the single multifractal analysis and densities.…”
Section: Discussionmentioning
confidence: 99%
“…Wavelet analysis is a powerful tool for investigating the multiscale nature and scaling behavior of hierarchical systems (Mallat, ), thus providing an appropriate framework for both the local Hurst detection (LHD) and local singularity analysis (LSA) of fractal signal records (Chen & Cheng, ). Notably, within the context of fractals, the Hurst index characterizes the persistence or intermittency of time series, while the singularity index is for the clustering or accumulation of mass or energy.…”
Section: Research Materials and Methodsmentioning
confidence: 99%
“…Wavelet transform (WT) is a popular method for time series analysis (e.g., trend, cycle, and correlation) of diverse geological or geophysical records (Dashtian et al, 2015;Kumar & Foufoula-Georgiou, 1997), including various isotope signals (Prokoph et al, 2004;Prokoph & Puetz, 2015). In addition, WT advances the scaling analysis of hierarchical structures and transient phenomena (Chen & Cheng, 2017). In this study, we use WT to obtain the local fractal sequence of U-Pb age distribution and δ 18 O time series based on the fractal modeling of large data sets complied from the literatures.…”
Section: Introductionmentioning
confidence: 99%